Understanding Employee Voice Cross Culturally: Does Being Collectivist Matter? - Unler, Ela; Caliskan, Sibel (Oeconomica Publishing House, 2017)
Analysis of employee voice has focused on the reasons and managerial issues regarding available environment to speak up. The study aims to understand the effect of management attitude on employee voice with the mediating effect of individual's perceived psychological safety. Besides, the role of job satisfaction and being individualist/collectivist as moderators over the effect of psychological safety on employee voice are analyzed. We constructed a framework based on Maynes and Podsakoff (2014)(3')s view that identifies four different types of voice behavior (supportive, constructive, defensive, and destructive). 207 questionnaires were collected from employees who are working in telecommunication industry. Based on analysis, positive management attitude facilitates supportive/constructive voice and reduces deconstructive voice. Perceived psychological safety mediates the relationship with management attitude and destructive voice. Also, job satisfaction level facilitates supportive/constructive voice and reduces deconstructive voice. Collectivism level of employees' moderates perceived psychological safety and deconstructive employee voice. Supported assumptions were discussed based social exchange theory and signaling theory. This study is one of the first that integrates not only constructive but also deconstructive voice into the model.
International Business and Management Conference -- NOV 11-12, 2016 -- Univ Econ, Prague, CZECH REPUBLIC
Keywords: Employee Voice; Psychological Safety; Management Attitude; Job Satisfaction; Collectivism; Psychological Safety; Behavior; Exchange; Work; Individualism; Determinants; Antecedents; Commitment; Responses; Speaking